2004
DOI: 10.1084/jem.20030851
|View full text |Cite
|
Sign up to set email alerts
|

Bone Marrow Allograft Rejection Mediated by a Novel Murine NK Receptor, NKG2I

Abstract: Natural killer (NK) cells mediate bone marrow allograft rejection. However, the molecular mechanisms underlying such a rejection remain elusive. In previous analyses, it has been shown that NK cells recognize allogeneic target cells through Ly-49s and CD94/NKG2 heterodimers. Here, we describe identification and characterization of a novel murine NK receptor, NKG2I, belonging to the NKG2 family. NKG2I, which was composed of 226 amino acids, showed ‫ف‬ 40% homology to the murine NKG2D and CD94 in the C-type lect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 31 publications
0
14
0
Order By: Relevance
“…Compared to inhibitory receptors, NK cell activating receptors on the whole are less well characterized, thus the receptor-ligand pair that triggers NK cell rejection of cardiac allografts may be difficult to identify. It has recently been reported that KLRE-1 (NKG2I) is required for NK cell rejection of H-2 d bone marrow transplants (36). While the ligand for NKG2I remains unknown, it may play a role in cardiac rejection.…”
Section: Nk Cells Promote Alloresponsesmentioning
confidence: 99%
“…Compared to inhibitory receptors, NK cell activating receptors on the whole are less well characterized, thus the receptor-ligand pair that triggers NK cell rejection of cardiac allografts may be difficult to identify. It has recently been reported that KLRE-1 (NKG2I) is required for NK cell rejection of H-2 d bone marrow transplants (36). While the ligand for NKG2I remains unknown, it may play a role in cardiac rejection.…”
Section: Nk Cells Promote Alloresponsesmentioning
confidence: 99%
“…Splenic NK, spleen, bone marrow, and liver mononuclear cells were separated and stained with the appropriate antibodies as described 13,15 ; phycoerythrin (PE)-anti-DX5, cyanin 5 (Cy5)-anti-T-cell receptor ␤ (TCR␤), Cy5-anti-CD3⑀ (PharMingen, San Jose, CA), and Cy-5-labeled antibody against KLRE-1 (anti-NKG2I: 7E8) were used. 13 …”
Section: Cell Preparation and Flow Cytometrymentioning
confidence: 99%
“…KLRE-1 genomic clone was isolated from a mouse genomic library using the KLRE-1 cDNA as a probe (cDNA sequence, first described by Koike et al 13 ). The genomic DNA fragment from NsiI site located at 1.5 kb upstream of the exon 2 (which contains ATG for first methionine) to BglII site present at 5.0 kb downstream of the exon 2 was used to construct the targeting vector ( Figure 1A).…”
Section: Construction and Establishment Of Egfp-klre-1 Knock-in Micementioning
confidence: 99%
See 2 more Smart Citations